Comparative karyological analysis of four diplozoid species (Monogenea, Diplozoidae), gill parasites of cyprinid fishes - Košková, Eva; Spakulová, Marta; Koubková, Božena; Reblánová, Marianna; Orosová, Martina (Parasitology research, 2011)
The present study has revealed new data on chromosome complements of diplozoid parasites, namely Diplozoon paradoxum from freshwater bream Abramis brama, Paradiplozoon bliccae from white bream Blicca bjoerkna, Paradiplozoon sapae from white-eye bream Ballerus sapa, and Paradiplozoon nagibinae from zope Ballerus ballerus. Particularly, D. paradoxum is characterized by four pairs (2n=8) of long (up to 22.1 μm) chromosomes: pairs 1, 2, and 3 are metacentric and pair 4 acrocentric. Karyotypes of three Paradiplozoon species are nearly identical in number and morphological classification of chromosomes, each comprising diploid number of 14 one-armed chromosomes of very similar length ranging up to 12.5 μm in P. bliccae, 9.2 μm in P. sapae, and 9.9 μm in P. nagibinae. All four species are similar in their total complement length, ranging from 64.4 to 50.4 μm. Interspecific differences were found in location of secondary constriction: it is situated on short arm of the 1st chromosome pair in D. paradoxum, on long arm of the 7th pair in P. bliccae and on long arm of the 4th pairs in P. sapae and P. nagibinae. Phylogenetic interrelationship within the diplozoids and hypothetic karyotype evolution is here discussed.
Keywords: ploštěnci; karyotypizace; nemoci ryb; Platyhelminths; Animals; Fish Diseases; Cestode Infections; Gills; buněčné jádro; žábry; Cell Nucleus; zvířata; Karyotyping; cestodózy; Cyprinidae